Study of the TiC Coating on Powder Metallurgy Diamonds Tool's Performance - Oliveira,Luciano José de (2015)
Some diamond tools use iron in their composition, and it is known that iron is a strong catalyst for the graphitization of diamonds. This graphitization occurs mainly during the processing of composite materials - conventional sintering or hot pressing, and during cutting operations. This work studies the effect of TiC coating on diamond, on structure, microstructure and mechanical properties of the processed composites. Samples were prepared by mixing powders of Fe (40 μm) and diamond (425 μm), and subsequent hot pressing at 35MPa/900 °C, during 3 minutes. Microstructural aspects were observed by SEM, and iron diffusion on diamond was studied by EDS. Structural analyses were performed by X-ray diffraction and Raman spectroscopy. Compressive tests were carried out, as well as the wear resistance of the diamond composites. The importance of employing coated diamonds was stablished. It was observed that iron did not activated the graphitization of diamond crystals.